Allergy to Fungi in Veterinary Medicine: Alternaria, Dermatophytes and Malassezia Pay the Bill! - Luís Miguel Lourenço Martins (Journal of Fungi, 2022)
The fungal kingdom comprises ubiquitous forms of life with 1.5 billion years, mostly phytopathogenic and commensals for humans and animals. However, in the presence of immune disorders, fungi may cause disease by intoxicating, infecting or sensitizing with allergy. Species from the genera Alternaria, Aspergillus and Malassezia, as well as dermatophytes from the genera Microsporum, Trichophyton and Epidermophyton, are the most commonly implicated in veterinary medicine. Alternaria and Malassezia stand as the most commonly associated with either allergy or infection in animals, immediately followed by Aspergillus, while dermatophytes are usually associated with the ringworm skin infection. By aiming at the relevance of fungi in veterinary allergy it was concluded that further research is still needed, especially in the veterinary field.